Defending professionalism a resource for librarians, information specialists, knowledge managers, and archivists - Crowley, William A. 1949-. (Santa Barbara, Calif. Libraries Unlimited, 2012)
"This book provides overdue guidance for demonstrating and preserving library, information, knowledge, and archival professionalism in American, British, and Canadian communities and organizations"--Provided by publisher.
Why Are We Trashing the Professionalism of Librarians, Information Specialists, Knowledge Managers, and Archivists? / Bill Crowley -- Justifying Professional Education in a Self-Service World / Rachel Rubin and Richard Rubin -- Youth Services in Public Libraries : A Return to Belligerence / Janice M. Del Negro -- We Build Communities through Knowledge : Demonstrating the Value of the Professional Public Librarian / Brenda Roberts -- Strategies and Aspirations for Defending School Library Professionalism / Don Hamerly -- Future-Proofing the Academic Librarian / Lenora Berendt and Maria Otero-Boisvert -- Understanding the Worth of the Professional Librarian in the Research University or Institution / Cleo Pappas -- Valuing the Return on Investment of the Information Professional in Specialized Institutions (Corporations, Government Agencies, NGOs, etc.) / Michael Koenig -- Defending the "Professional" Archivist / Cecilia Salvatore -- A Culturally Pragmatic and Feminist Influenced Approach to Defending Professionalism / Bill Crowley -- The LIS Professional Commons and the Online Networked Practitioner / Kyle M.L. Jones and Michael Stephens -- The "Political Case" for Supporting the Value of Professionalism / Bill Crowley -- An Obstacle : The Difficulty of Convincing Others to Change Their Thinking and Behavior / Robert F. Moran Jr. -- Advancing Professionalism in Library, Information, Knowledge, and Archival Services in the "New Normal World" / Bill Crowley.
Keywords: Libraries and society; Library education; Librarians -- Professional ethics; Information scientists -- Training of; Information scientists -- Professional ethics; Knowledge workers -- Training of; Knowledge workers -- Professional ethics; Archivists -- Training of; Archivists -- Professional ethics